Galaxy Clusters Selected with the Sunyaev-Zel'dovich Effect from 2008 South Pole Telescope Observations - Vanderlinde, K; Crawford, T. M; de Haan, T; Dudley, J. P; Shaw, L; Ade, P. A. R; Aird, K. A; Benson, B. A; Bleem, L. E; Brodwin, M; Carlstrom, J. E; Chang, C. L; et al. (The Astrophysical journal, 2010)
We present a detection-significance-limited catalog of 21 Sunyaev-Zel'dovich-selected galaxy clusters. These clusters, along with one unconfirmed candidate, were identified in 178 deg2 of sky surveyed in 2008 by the South Pole Telescope (SPT) to a depth of 18 Delta *mK arcmin at 150 GHz. Optical imaging from the Blanco Cosmology Survey (BCS) and Magellan telescopes provided photometric (and in some cases spectroscopic) redshift estimates, with catalog redshifts ranging from z = 0.15 to z>1, with a median z = 0.74. Of the 21 confirmed galaxy clusters, 3 were previously identified as Abell clusters, 3 were presented as SPT discoveries in Staniszewski et al., and 3 were first identified in a recent analysis of BCS data by Menanteau et al.; the remaining 12 clusters are presented for the first time in this work. Simulated observations of the SPT fields predict the sample to be nearly 100% complete above a mass threshold of M 200 5 X 1014 M h --1 at z = 0.6. This completeness threshold pushes to lower mass with increasing redshift, dropping to ~4 X 1014 M h --1 at z = 1. The size and redshift distribution of this catalog are in good agreement with expectations based on our current understanding of galaxy clusters and cosmology. In combination with other cosmological probes, we use this cluster catalog to improve estimates of cosmological parameters. Assuming a standard spatially flat wCDM cosmological model, the addition of our catalog to the WMAP seven-year results yields Delta *s8 = 0.81 ? 0.09 and w = --1.07 ? 0.29, a ~50% improvement in precision on both parameters over WMAP7 alone.